Reminiscence through the Lens of Social Media - Thomas, Lisa; Briggs, Pam (Frontiers in Psychology, 2016)
Reminiscence is used to support and create new social bonds and give meaning to life. Originally perceived as a preoccupation of the aged, we now recognize that reminiscence has value throughout the lifespan. Increasingly, social media can be used to both support and prompt reminiscence, with Facebook’s Lookback or Year in Review as recent examples. This work takes prompted reminiscence further, asking what forms and functions of reminiscence are supported by social media. Utilizing the online service MySocialBook, we invited participants to curate content from their personal Facebook account to then be transformed into a printed book. We used that book as a prompt for discussion of the reminiscence function of the curated material, using Westerhof & Bohlmeijer’s (2014) reminiscence framework as a starting point. We conclude that this framework is valuable in understanding the role of social media in reminiscence, but note that earlier models, such as Webster’s Reminiscence Functions Scale, are also relevant. We contribute to the reminiscence debate by adding a technological lens to the process of life review, whilst concurring with other researchers in this field that a robust conceptual framework is lacking, particularly when considering the forms of reminiscence that are most salient for younger people.